2015
DOI: 10.1186/s13014-015-0379-7
|View full text |Cite
|
Sign up to set email alerts
|

Lobular carcinoma in situ (LCIS) of the breast: is long-term outcome similar to ductal carcinoma in situ (DCIS)? Analysis of 200 cases

Abstract: BackgroundLobular carcinomas in situ (LCIS) represent 1-2% of all breast cancers. Both significance and treatment remain widely debated, as well as the possible similarities with DCIS.Materials and methodsTwo hundred patients with pure LCIS were retrospectively analyzed in seven centres from 1990 to 2008. Median age was 52 years; 176 patients underwent breast-conserving surgery (BCS) and 24 mastectomy. Seventeen patients received whole breast irradiation (WBRT) after BCS and 20 hormonal treatment (15 by tamoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…9 Especially while considering management, both PLCIS and FLCIS are considered aggressive LCIS subtypes. 5 In conclusion, we report distinct recurrence patterns of NCLCIS.…”
Section: Dcismentioning
confidence: 54%
“…9 Especially while considering management, both PLCIS and FLCIS are considered aggressive LCIS subtypes. 5 In conclusion, we report distinct recurrence patterns of NCLCIS.…”
Section: Dcismentioning
confidence: 54%
“…As a strategy of risk reduction, LCIS patients with higher risk, such as women with BRCA 1 or BRCA 2 genetic mutations, may undergo bilateral prophylactic mastectomy [10]. There is limited support for the addition of radiation therapy, but a small cohort study suggested some benefits [13]. Based on the more recent findings of Taylor et al [29], there was no significant difference in overall survival between patients who received lumpectomy alone or lumpectomy with radiation treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This abnormal proliferation of cells frequently originates in the terminal ductal lobular unit of the breast and may spread to the ducts [12]. LCIS may also be associated with the development of invasive ductal carcinoma, typically estrogen receptor-positive (ER+) lesions [13].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the risk of invasive disease increases when there is an association with other lesions, such as ductal hyperplasia, or first-degree family history of invasive cancer. 6 Patients are offered one of three treatment options: lifetime monitoring to detect subsequent malignancy at an early stage; chemoprevention, with tamoxifen being the most used drug, as it reduces the risk of developing cancer in the subsequent four years by 56%; or prophylactic bilateral mastectomy. 26 Additionally, for patients with a positive classical LCIS margin, as in the present case, there is no consensus regarding reoperation, though 7% to 53% of surgeons choose to reoperate.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis is usually more common among 40-to 50-year-old women, 5 15 years prior to the mean age at which an invasive carcinoma occurs 2,3 and 7 to 8 years earlier than the occurrence of ductal carcinoma in situ (DCIS). 6 Keywords ► breast ► cancer ► breast ultrasound ► mammography…”
Section: Introductionmentioning
confidence: 99%